مقارنة المكافحة البيولوجية والمكافحة الكيميائية في المرحلة الخضرية والإنتاجية لنبات الطماطم - ايمان عطيالله; ليلى حوبه; نسرين مسعودي (Université of Eloued, 2025)
This research deals with the study of the effect of some medicinal plants (fenugreek, garlic and onions) and their combination on the growth and quality of the tomato plant (Solanum lycopersicum)and comparing them with chemical treatments, with the aim of using them as natural and safe alternatives to chemical pesticides. Tomatoes were planted between two lines of garlic and the same in fenugreek and onions, as well as planted between a mixture of these plants and sprayed in the vegetative stage with the extract of these plants, and several criteria were applied to them, including (stem length, leaf area, number of flowers, fruit weight, fruit size, flavonoids, polyphenols, concentration of heavy metals......). The results of the field study showed that the vegetative growth was the highest in the onion plant treatment followed by the treatment with the mixture, the fruit size was the highest during chemical treatment, the secondary metabolites of flavonoids and polyphenols were the highest in chemical treatment and with the concentration of heavy metals, and this shows that the natural treatment of plants used in the experiment had a positive effect on the vegetative and productive phase of tomatoes, and also had a positive effect on the lack of toxic heavy metals of this plant. From it we say that the natural extracts of these plants improve and increase the resistance of tomatoes to diseases, enhance the quality of fruits and their nutritional value, and reduce their contamination with heavy metals.
Toxicologie
Keywords: biological; chemical control; tomato plant Solanum lycopersicum.